Presence of Multidrug Resistance (MDR) Escherichia coli in the Citarum River located in Greater Bandung Area, Indonesia - Megantara, Imam; Muhtado, Azmi Raffi; Pradini, Gita Widya; Goenawan, Hanna; Sylviana, Nova (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: One of the main problems of the Citarum River is the contamination of E. coli due to livestock activities, washing toilets, and industry. In addition, irrational use of antibiotics in the community and livestock can increase E. coli resistant strains to antibiotics. This study aimed to identify the presence of multidrug resistance (MDR) and extended-spectrum β-lactamase (ESBL) E. coli strains in Citarum river clusters, namely industrial, livestock, and residential clusters.Methods: This was a descriptive study. A sample of 100 mL surface water from each Citarum cluster. Culture, antibiotic sensitivity test, and PCR to identify blaCTX-M-15 gene carriers of ESBL E. coli were carried out in the sample.Results: There were 37 isolates of E. coli, with 24% of these isolates showing MDR properties, which can be found in industrial, livestock, and residential clusters at 13%, 8%, and 3% respectively. The most E. coli-resistant antibiotics found in these samples were ampicillin (45%), followed by tetracycline (37%), and azithromycin (29%). The PCR examination did not find the blaCTX-M-15 gene carrying ESBL properties in all three Citarum river clusters.Conclusion: The presence of E. coli isolates in each Citarum river cluster suggests the occurrence of river pollution due to animal, human or industrial waste. Therefore, it is necessary to make better government regulations regarding sanitation and education for the surrounding community regarding the importance of keeping the river clean.